2014
DOI: 10.31018/jans.v6i2.517
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of cow urine based eco-friendly formulations against Spilarctia obliqua (Walker)

Abstract: Abstract:The laboratory studies were conducted to assess the bio-efficacy of cow urine and jatropha seed extracts prepared in water and cow urine (@ 5% and @10% against different stages of Spilarctia obliqua. The cent per-cent mortality of neonate larvae was observed in jatropha seed water extract @10% followed by significantly less larval survival in cow urine @10% (13.35%), jatropha seed cow urine extract @10% (16.64%) in comparison to untreated control (93.32%).Similarly cent per cent larval mortality of 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…A similar report also demonstrated that cow urine in garlic paste caused 75.96% reduction 10 days after the spray [58]. Several other reports have described the effectiveness of cow urine in insect pest management on different crop plants [25,[59][60][61]. Besides crop protection against insect pests, cow urine (50%) was also shown to increase the chlorophyll and protein content in Bhindi crops, as it enhances the NPK uptake through the foliar spray and, thus, the crop yield [57,62].…”
Section: Discussionmentioning
confidence: 77%
“…A similar report also demonstrated that cow urine in garlic paste caused 75.96% reduction 10 days after the spray [58]. Several other reports have described the effectiveness of cow urine in insect pest management on different crop plants [25,[59][60][61]. Besides crop protection against insect pests, cow urine (50%) was also shown to increase the chlorophyll and protein content in Bhindi crops, as it enhances the NPK uptake through the foliar spray and, thus, the crop yield [57,62].…”
Section: Discussionmentioning
confidence: 77%
“…Cow urine is known to be effective against insect pests. The oviposition deterrence of cow urine is not known but insecticidal activity against Bihar hairy caterpillar Spilarctia oblique sprayed @10% (Geetanjaly and Tiwari, 2014), Spodoptera litura @20% (Naik and Tiwari, 2018), sorghum shoot fly, Atherigona soccata @5% (Mudigoudra et al, 2009) is documented. Darekastra also possess the oviposition deterrence that can be attributed to its composition and mode of action of M. azedarach.…”
Section: Resultsmentioning
confidence: 99%